Spontaneous perirenal urinoma induced by NSAID-associated acute interstitial nephritis - Chang H; Kuei C; Tseng C; Hou Y; Tseng Y (Dove Medical Press, 2018)
Hsiu-Wen Chang,1 Chia-Hao Kuei,2 Chin-Feng Tseng,1 Yi-Chou Hou,3 Ying-Lan Tseng1 1Department of Internal Medicine, Cardinal Tien Hospital, School of Medicine, Fu-Jen Catholic University, Xin-dian District, New Taipei City, Taiwan, Republic of China; 2Division of Urology, Department of Surgery, Cardinal Tien Hospital, New Taipei City, Taiwan, Republic of China; 3Department of Internal Medicine, Cardinal Tien Hospital An-Kang Branch, School of Medicine, Fu-Jen Catholic University, Xin-dian District, New Taipei City, Taiwan, Republic of China Abstract: Urinoma, defined as the urine leakage beyond the urinary tract, is commonly induced by blunt trauma or urinary tract obstruction by stone, intra-abdominal malignancy, or retroperitoneal fibrosis. Spontaneous urinoma is rare and parenchymal pathologic change is rarely mentioned when urinoma is found. We present a case of a 28-year-old woman with bilateral flank pain induced by spontaneous urinoma. The lady received chronic analgesics because of migraine. After intravenous ketorolac injection, bilateral perirenal urinoma developed. Renal biopsy showed acute interstitial nephritis associated with nonsteroid anti-inflammatory drug (NSAID). After discontinuing the medication, urinoma subsided, and the patient was discharged with normal serum creatinine. This was the first case of urinoma induced by NSAID-related interstitial nephritis, and pathophysiology and management of spontaneous urinoma are discussed. Keywords: spontaneous urinoma, NSAID, interstitial nephritis, acute kidney injury, ketorolac